The Impact of Resident Duty Hour and Supervision Changes: A Review. Issue 1 (January 2016) - Greenberg, William E.; Borus, Jonathan F.
Abstract : Abstract: In 2003 and again in 2011, the Accreditation Council for Graduate Medical Education (ACGME) instituted increasingly stringent requirements governing resident hours and supervision, with the goals of improving patient safety, resident well-being, and resident education. Although the changes initially stemmed from a catastrophic outcome in a patient treated with psychotropic medications and behavioral restraints, and have been in place over a decade, many psychiatrists are not familiar with these changes and with their potential effects and "side effects" on today's trainees and faculty. The authors review the history leading to these changes, summarize the revised requirements, and review representative literature regarding the impact of the changes. The existing studies of the impact of the new requirements on improving patient safety, resident well-being, and resident education are inconclusive, and most editorials, perspectives, and surveys of faculty and residents reflect a lack of enthusiasm for the changes. They go on to suggest the need for evidence-based outcome studies prior to the institution of further major changes in ACGME requirements.